Performance comparison between commercial Dye and natural Dye based from Dye-sensitized solar cell using titanium graphene film / Siti Zubaidah Mohamed Siddick - Siti Zubaidah, Mohamed Siddick (2018)
Dye-sensitized solar cell (DSSC) has attracted interest in the renewable energy community due to the ability of the photoelectrochemical device for converting sunlight directly to electricity with easy fabrication process and known as a low-cost solar cell. In this present study, the performance of DSSC based on graphene-titania (TrGO) photoanode using conventional N719 (synthetic dye), natural red anthocyanin dye (organic dye) and natural green chlorophyll dye (organic dye) were extensively studied, analyzed and discussed. One of the main components in DSSC is the dye sensitizer where it is the main contributor to the photovoltaic characteristic efficiency. Dyesensitized must possess wider absorption spectra to maximize the absorption of light. Nowadays, extensive study of natural dyes DSSC conducted due to its promising alternative to conventional synthetic sensitizer because they are inexpensive, flexible, abundant, suitable, and reduce the usage of noble metals. However, to increase the performance of natural dye-based DSSC, an efficient isolation and fast extraction methods for purification were explored with the ability of the natural dye attached to the semiconductor oxide photoanode. Dye acts as an electron contributor to the semiconductor oxide surface. A highly conductive surface of photoanode is needed to ensure the photogenerated electron travels efficiently. By introducing rGO to the TiO2 semiconductor oxide, rGO network will lower down the electron migration length of the nanocrystalline TiO2 semiconductor oxide. TrGO was successfully synthesized via onestep sol precipitation peptization technique using titanium (IV) isopropoxide (TTIP) and reduced graphene oxide (RGO) was used as starting materials. In this thesis, the first parameter covers on to achieve the best nanocomposite morphology an film is the different weight ratio of rGO in the photoanode. A continuous effort was made to further improve on the synthesis pH of the nanocomposite and lastly, the calcination temperature (400 oC and 450 oC) was explored to attain the best anatase crystalline phase for the nanocomposite film. From the modification, the best performance DSSC was TrGO-3 with pH3 photoanode. It was found TrGO works with all type of dye (commercial N719 dye, red anthocyanine dye, and green chlorophyll dye). Green chlorophyll dye exhibit 4.77mAcm-2 current density with the efficiency of 1.41% and red anthocyanin dye producing 4.08 mAcm-2 current density with the efficiency of 1.36% compared to commercial N719 dye with 12.98 mAcm-2 current density with the efficiency of 4.79 %. Although natural dye (green chlorophyll dye and red anthocyanin dye) shows lower efficiency compared to commercial N719 dye, natural dye exhibits good properties such as environmentally friendly, cheap, abundant and good in energy production if numerous study is conducted to improving the energy production. Energy band gap of the device also shows improvements than pure TiO2 where it lowers down from 3.2eV to 2.82eV for TrGO-3 and 2.72eV for TrGO 3 450. In terms of photovoltaic efficiency, TrGO-3 shows the best characteristics with the highest efficiency 4.76 %, with 695.81mV for Voc and current density, Jsc of 12.98mAcm-2. The enhancement of DSSC mainly contributes from the integration of conductive rGO to TiO2 where it contributed to the enhancement in porosity on the surface of the semiconductor oxide. Porosity helps in increasing the dye loading and thus enhancing the photovoltaic characteristics. The electron lifetime also obtained to prove the improvement in DSSC performance when rGO incorporated in TiO2 photoanode in terms of reducing electron loss between the surface interface and lower down electron migration length.